Improvement of efficiency of use of liquid-glass mixtures Part 3. Nanodispersed materials - A. N. Krutilin; Yu. Yu. Huminski; O. A. Rusevich; L. V. Kulbitskaya (Литьë и металлургия, 2018)
The mechanisms of interaction of various ultradisperse substances with molding materials, as well as their influence on physical and technological properties, are considered. Examples of using of ultrafine nano-sized additives in foundry are given. The possibilities of increasing level of technological properties (initial strength, gas permeability and non-stick properties) of mixtures due to additives of UPC, which contributes the improvement of the surface quality of castings and to the reduction laboriousness of finishing operations are described.